ANALYSIS OF E-CRM, E-MARKETING ON CUSTOMER LOYALTY WITH INTERVENING VARIABLES OF CUSTOMER SATISFACTION AT PT. INDOFOOD CBP SUKSES MAKMUR Tbk. - Yuliati Yuliati; Ratih Hurriyati; Moch. Adieb Sultan (Dinasti Publisher, 2021)
The purpose of this study was to determine the effect of E-CRM and E-Marketing on customer loyalty and intervening satisfaction of consumers of PT. Indofood. In this study, the authors use Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach to answer research problems related to the effect of E-CRM and E-Marketing on customer loyalty with the intervening variable of customer satisfaction. This study indicates that based on the results of hypothesis testing, E-CRM affects customer loyalty with the intervening variable of customer satisfaction, as well as the results of testing the hypothesis that E-Marketing affects customer loyalty with the intervening variable of customer satisfaction.